Acute and chronic oral toxicity of standardized water extract from the fruit of Phyllanthus emblica Linn - K. Jaijoy (2018)
Phyllanthus emblica Linn. (Euphorbiaceae) is an herbal plant commonly used in Asian traditional medicine systems for treatment of many disorders. In the present study, we investigated for the first time acute and chronic toxicity of the standardized water extract of P. emblica fruit. The water extract of P. emblica was prepared according to the Thai Herbal Pharmacopoeia and standardized to 20% gallic acid. For studying acute toxicity study, single oral dose of 5000 mg water extract /kg body weight was administered to Sprague Dawley rats (five females, five males). The results showed no toxicity in terms of general behavior change, mortality, or change in gross appearance of internal organs (LD50> 5,000 mg/kg). Chronic toxicity was studied by daily oral dose (ten females, ten males) of 300, 600 and 1,200 mg/kg for 270 days. The results showed slightly significant differences in the body and organ weights between the control and treatment groups. In addition, the rats were analyzed for final body and organ weights, necropsy, and hematological, blood chemical and histopathological parameters. Hematological analysis and clinical blood chemistry revealed slightly changes, but were within the normal limits. No gross or histopathology findings were observed in the treatment groups. Altogether, the standardized water extract from the fruit of P. emblica did not produce acute and chronic toxicity in its traditional uses. Industrial relevance: Traditional medicine is still stronghold of more than 50% of the world population, especially in developing countries. Nowadays, a number of medicinal plants (such as Phyllanthus emblica Linn.) are commercially available on local markets as a tonic, food and/or dietary supplement product commonly used for clinical management of several conditions. Despite the widespread use of this plant, there is still little literature on the scientific evaluation of their toxicity. Results of the current study provide pivotal evidences for ascertaining the safety of the stardardized water extract of P. emblica fruit that could be used as food supplements, dietary supplements, etc. in folkloric medicine. © 2010 Healthy Synergies Publications.